Penggunaan Zeolit sebagai Adsorben untuk Penjernihan Air Sumur terhadap Kandungan Logam Fe, Nilai BOD, COD, dan TSS di Kelurahan Kampuang Jua Nan XX, Kecamatan Lubuk Begalung, Kota Padang - Zilfa, Z.; Yusuf, Yulizar; Syahputra, Dian (Departemen Kimia Universitas Andalas, 2024)
Nobita Hill is an area that will be used as a tourist destination located in Kampung Jua Nan XX Village, at the foot of Nobita Hill, precisely in RW III, there are many houses with poor well water quality. The purpose of this study is to determine the use of zeolite (adsorbent) to purify well water based on Fe metal content parameters, BOD, COD, TSS values and also to determine the effect of adsorbent mass, sample volume, contact time and stirring time on the adsorption process. Determination of Fe content using atomic absorption spectrophotometry (AAS). Determination of the value of Biological Oxygen Demand (BOD) using the Iodometric titration method, determining the value of Chemical Oxygen Demand (COD) using the visible spectrophotometric method and determining the value of Total Suspended Solids (TSS) using the gravimetric method. Zeolite was characterized by X-Ray Fluorescence (XRF) before and after adsorption. Analysis of the concentration of Fe in well water before adsorption 2.1 mg/L. 40 mL of well water was adsorbed with 0.1 g of zeolite for 45 minutes at a stirring speed of 200 rpm, Fe decreased by 96.1%, from 2.1 mg/L to 0.1 mg/L. COD, BOD and TSS values also decreased 57.1%, 63.9% and 67.5% respectively. Characterization using XRF showed a decrease in Si and Al content and an increase in Fe metal content in the adsorbent after adsorption.